Dysregulation of glutaminase and glutamine synthetase in cancer. - Mates-Sánchez, José Manuel; Campos-Sandoval, José Ángel; De los Santos-Jiménez, Juan; Márquez-Gómez, Javier (Elsevier, 2019)
Besides fast glucose catabolism, many types of cancers are characterized by elevated glutamine consumption. Medical oncology pursuits to block specific pathways, mainly glycolysis and glutaminolysis, in tumor cells to arrest cancer development. This strategy frequently induces adaptive metabolic resistance that must be countered. Combination therapy is an anticancer synergistic tool to overcome both cancer growth and resistance mechanisms. Dysregulation of glutaminase and glutamine synthetase are key events that allow anabolic adaptation of tumors. Several specific drugs that inhibit metabolic enzymes dealing with glutamine metabolism have been able to eliminate some neoplasms. Targeting the tumor microenvironment can be also another essential factor to be taken into account when single or combined cancer metabolic therapy fails.
https://openpolicyfinder.jisc.ac.uk/id/publication/12488
Keywords: Cáncer - Aspectos moleculares; Cancer metabolism; Combination therapy; Glitaminase isoenzymes; Glutamine; Glutamine Synthetase; Synergistic inhibitors